Measurement Model of Technopreneurship Intentions and the Performance of Electrical Lighting Installation Practices in Vocational High School - Husna, Amelia Fauziah; Sofyan, Herminarto (DPTE FT UNY, 2023)
The aims of this study are to produce measurement model of the intention of technopreneurship and the performance of the practice of electric lighting installations. Analysis of the data used is confirmatory factor analysis. Confirmatory Factor Analysis has several stages to determine the results. These stages include determining goodness of fit, calculating path estimation, calculating loading factor, Average Variance Extracted (AVE), and calculating reliability using Construct Reliability (CR). Goodness of fit is determined by looking for the Goodness-of-Fit Index (GFI), Norm Fit Index (NFI), Comparative Fit Index (CFI), or Root-Mean-Square Error of Approximation (RMSEA). CFI, RMSEA, loading factor, and tcount values met the suitability index criteria. These results indicate that the model for measuring technopreneurship intention variables and the performance of electrical lighting installation practices theoretically matches the field data, so that the measurement model is acceptable.